2009
DOI: 10.1021/op9001609
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Sequential Palladium-Catalyzed Cross-Coupling Reactions in the Stereospecific Synthesis of Trisubstituted Olefins

Abstract: In the article they were spelled incorrectly as Didier Shilds and Wim Vermuelen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The literature shows it and its substituted analogs being used in the synthesis of allenes, 1 Nheterocyclic carbenes, 2 and substituted furans 3 and as a reactant in Sonogashira cross-couplings. 4 Its polymerization is well known and has been studied with various catalysts. 5 However, under certain conditions, propargyl alcohol can also decompose explosively, resulting in destructive force; its detonation has been previously studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The literature shows it and its substituted analogs being used in the synthesis of allenes, 1 Nheterocyclic carbenes, 2 and substituted furans 3 and as a reactant in Sonogashira cross-couplings. 4 Its polymerization is well known and has been studied with various catalysts. 5 However, under certain conditions, propargyl alcohol can also decompose explosively, resulting in destructive force; its detonation has been previously studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Houpis et al reported an unexpected exotherm during the synthesis of the active pharmaceutical ingredient 64 via the Sonogashira cross-coupling of bromide 61 with propargyl alcohol (62) (Scheme 17). 59 More specifically, during a reaction involving ca. 100 g of bromide 61 in which all of the reaction components were mixed at room temperature in a 2 L reactor and heated to 70 °C, an abrupt temperature rise to 145 °C was observed along with visible formation of dark polymeric material.…”
Section: Introductionmentioning
confidence: 99%